Evaluation of strategies for the physical activity promotion: Cost-utility study - Sposito, L. A.C. [UNESP]; Nakamura, P. M.; Monteiro, H. L. [UNESP]; Papini, C. B. [UNESP]; Benedetti, T. R.B. [UNESP]; Kokubun, E. [UNESP] (Servicio de Publicaciones de la Universidad Autonoma de Madrid, 2021)
The aim was to compare the additional cost by Quality Adjusted Life Years (QALY) gained from three strategies for physical activity promotion and verify the interventions influence on the percentage of physically active adults in Basic Health Units (BHU). BHU users were randomized into three groups: (a) brief counseling-received guidelines to increase physical activity (PA) time; (b) indication group to the supervised physical exercise program-was invited to participate in the physical exercise program at the BHU; and, (c) evaluation group – didn’t receive any type of intervention and only answered the questionnaires proposed by the research. The individuals in the three groups were interviewed in five moments, during a year, being evaluated on the cost by QALY gained and PA time. The strategy of brief counseling was more effective when compared to the other strategies, due to the lower cost/QALY and indication of positive results on PA.
Evaluación de estrategias para la promoción de la actividad física: Costo-utilidad
Keywords: Counseling; Physical Activity; Primary Health Care and Brazil